GRAVITY WITH SCALAR FIELD VISCOUS FLUID - Myrzakul, S R; Imankul, M; Arzimbetova, M; Myrzakul, T R (Journal of Physics: Conference Series, 2021)
We focus on a viable teleparallel cosmological model with a scalar field in a flat Friedman-Robertson-Walker universe. The Lagrangian and equations of motion are obtained. The case of an inhomogeneous viscous dark energy is considered and the cosmological parameters associated with the viscosity parameter are determined. It is shown that when considering constant viscosity and state parameter, the Universe expands exponentially
Keywords: Type of access: Open Access; scalar field